1983
DOI: 10.1002/bit.260251223
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of cellulase from Trichoderma viride on cellulose

Abstract: The adsorption of cellulase from Trichoderma viride (Meicelase CEP) on the surface of pure cellulose was studied. The adsorption was found to obey apparently the Langmuir isotherm. From the data concering the effects of temperature and the crystallinity of cellulose on the Langmuir adsorption parameters, the characteristics of the adsorption of the individual cellulase components, namely CMCase (endoglucanase) and Avicelase (exoglucanase), were discussed. While beta-glucosidase also adsorbed on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(74 citation statements)
references
References 22 publications
3
65
0
4
Order By: Relevance
“…This estimation can be good only when a very low concentration cellulase is used for adsorption experiments because any small variations in free protein measurement may result in large deviations in calculated A max values in the first order equation for approximation of the Langmuir equation. Another deviation could be large especially for the easily hydrolyzed pretreated biomass studied here (COSLIF samples) because some hydrolysis occurs during the active stage of cellulase adsorption, even when experiments are carried out at a decreased temperature (Beldman et al, 1987;Ooshima et al, 1983;Steiner et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This estimation can be good only when a very low concentration cellulase is used for adsorption experiments because any small variations in free protein measurement may result in large deviations in calculated A max values in the first order equation for approximation of the Langmuir equation. Another deviation could be large especially for the easily hydrolyzed pretreated biomass studied here (COSLIF samples) because some hydrolysis occurs during the active stage of cellulase adsorption, even when experiments are carried out at a decreased temperature (Beldman et al, 1987;Ooshima et al, 1983;Steiner et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…But Ryu et al (1984) found that cellulase contained tightly adsorbed cellobiohydrolases, some loosely bound EG1, and nonadsorbed endoglucanases other than EG1. Ooshima et al (1983) found that the relative adsorption of T. viride endoglucanases and cellobiohydrolases was temperaturedependent, with endoglucanases preferentially adsorbed at 5jC, and cellobiohydrolases preferentially bound at 50jC. By contrast, Kyriacou et al (1989) found that adsorption of T. reesei CBH1 was stronger than adsorption of EG1-3 on Solka Floc at 5jC, but that preferential adsorption of CBH1 was diminished at 50jC, and such preferential adsorption was also observed to be less pronounced with decreasing ionic strength.…”
Section: Cellulase Adsorption Adsorptionmentioning
confidence: 96%
“…This observation led investigators in the 1980s to postulate a model for cellulose structure consisting of amorphous and crystalline fractions (Fan et al, , 1981Lee et al, 1983). If this hypothesis were correct, it would be expected that crystallinity should increase over the course of cellulose hydrolysis as a result of preferential reaction of amorphous cellulose (Betrabet and Paralikar, 1977;Ooshima et al, 1983). However, several studies have found that crystallinity does not increase during enzymatic hydrolysis (Lenze et al, 1990;Ohmine et al, 1983;Puls and Wood, 1991;Schurz et al, 1985;Sinitsyn et al, 1989).…”
Section: Crystallinity Index (Cri)mentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause for the rate reduction and low yield is not yet understood, and determining the primary mechanism will have important implications in the optimal design of an enzymatic hydrolysis process. Several possible reasons for the low rate and yield have been suggested in the literature: change of reactivity (Nidetzky and Steiner, 1993;Zhang et aI., 1999) and physical properties of substrate, such as crystallinity (Betrabet and Paralikar, 1977;Ooshima et al, 1983); change of specific surface area (SSA) during the reaction (Hong et aI., 2007); deactivation of enzyme as a result of mechanical mixing (Ganesh et aI., 2000;Ghadge et aI., 2005b;Kim et al ., 1982;Reese and Mandels, 1980); and inactivation of adsorbed enzymes (Jalak and Valjamae, 2010;Ma et aI., 2008;Valjamae et aI., 1998;Xu and Ding, 2007). A simplified scheme to produce ethanol from cellulosic substrate Nidetzky and Steiner (1993) and Zhang et ai.…”
Section: Introductionmentioning
confidence: 99%